2012
DOI: 10.1063/1.4752102
|View full text |Cite
|
Sign up to set email alerts
|

An initial and boundary-value problem for the Zakharov-Kuznestov equation in a bounded domain

Abstract: Motivated by the study of boundary control problems for the Zakharov-Kuznetsov equation, we study in this article the initial and boundary value problem for the ZK (short for Zakharov-Kuznetsov) equation posed in a limited domain = (0, 1) x × ( − π /2, π /2) d , d = 1, 2. This article is related to Saut and Temam ["An initial boundary-value problem for the Zakharov-Kuznetsov equation," Adv. Differ. Equ. 15(11-12), 1001-1031 (2010)] in which the authors studied the same problem in the band (0, 1) x × R d , d = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(77 citation statements)
references
References 15 publications
(8 reference statements)
2
75
0
Order By: Relevance
“…To prove the existence part of this theorem, we put α = 0 and use as in [29] a parabolic regularization of (2.1)-(2.3), that is, we consider for any (small) positive > 0 the following parabolic problem:…”
Section: Existence Theoremmentioning
confidence: 99%
See 2 more Smart Citations
“…To prove the existence part of this theorem, we put α = 0 and use as in [29] a parabolic regularization of (2.1)-(2.3), that is, we consider for any (small) positive > 0 the following parabolic problem:…”
Section: Existence Theoremmentioning
confidence: 99%
“…Our work was motivated by [29] on IBVP for (1.1) posed on a strip bounded in x variable and unbounded in y. Studying this paper, we have found that the term u xyy in (1.1) delivers additional "dissipation" which helped to prove decay of small solutions in domains of a channel type unbounded in x direction.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our work was motivated by the paper of Saut and Temam [22] on initial boundary value problem in a domain bounded in x variable and non-bounded in y variable. Studying this paper, we discovered that the term u xyy in ZK equation delivers additional "dissipation" which can help to prove decay of small solutions in non-bounded domains of a channel type non-bounded in x direction and we consider the following initial boundary value problem.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, the interest on dispersive equations became to be extended to multi-dimensional models such as the Kadomtsev-Petviashvili (KP) and ZK equations. As far as the ZK equation is concerned, the results on IVP and IBVP can be found in [8,9,11,21,23,15,18,26,22,31,32]. Our work has been inspired by [30] where (1.2) posed on a strip bounded in x variable was concerned with.…”
Section: Introductionmentioning
confidence: 98%